African Christianity's Disposition to African Identity and Sociological Matters Arising (2019)
Church historians, anthropologists, and sociologists, among others, have written extensively on the interface between African Christianity and African culture, with insignificant attention paid to the issue of identity. This paper, in the attempt at filling the lacuna in presious studies, examined generally the disposition of African Christianity particularly some selected Pentecostal churches to African‘s cultural and traditional religious identity with emphasis on their sociological implications. Leaning on interx’iews conducted with members of selected churches such as African Independent and Pentecostal churches such at Mountain of Fire and Miracle Ministries. The Apostolic Church. Christ Apostolic Church, and Living Faith Church in Ibadan, there is further explication of issues bothering on interface between African Christianity, cultural and traditional religious identity in Nigeria. Data obtained were analyzed using content analysis and discussed within the ambit of Emile Durkheim's functional theory of religion. Consequently, it is revealed that the teachings and practices of selected churches affected positively and negatively African cultural elements such as traditional names, marital statics and social grouping. This, therefore, calls for a review of the practical interface between African Christianity and African cultural practices in such a way that the two would harmoniously work towards the production of a society that blends tradition with modernity.